Technology spillovers, asset redeployability, and corporate financial policies - Phuong Anh Nguyen; Ambrus Kecskés (Asian Development Bank Institute (ADBI), 2021)
Prior research shows that technology spillovers across firms increase innovation, productivity, and value. We study how firms finance their own growth stimulated by technology spillovers from their technological peer firms. We find that greater technology spillovers lead to higher leverage. This is the result of technology spillovers increasing asset redeployability, as evidenced by more collateralized borrowing and asset transactions. Borrowing costs also decrease. Exogenous variation in the R&D tax credits of other firms allows us to identify the causal effect of technology spillovers on a given firm.
Keywords: G12; G31; G32; G33; G34; O31; O33; 330; innovation; technology spillovers; research and development; financial policies; capital structure; asset redeployability; cost of debt